Granulocyte-colony stimulating factor as treatment option in patients with recurrent miscarriage - Santjohanser, Claudia; Knieper, Catherine Linn; Franz, Cordula; Hirv, Kaino; Meri, Osama; Schleyer, Manfred; Würfel, Wolfgang; Toth, Bettina (Archivum immunologiae et therapiae experimentalis, 2013)
In 1-5 % of patients during childbearing years recurrent miscarriages (RM) occur. There are established risk factors like anatomical, endocrine and hemostatic disorders as well as immunological changes in the maternal immune system. Nevertheless, further elucidation of the pathogenesis remains a matter of debate. In addition, there are no standardized immunological treatment strategies. Recent studies indicate possible effects of tumor necrosis factor α blocker and granulocyte-colony stimulating factor (G-CSF) concerning live birth rate (LBR) in RM patients. Therefore, we performed a retrospective cohort study in patients undergoing assisted reproductive treatment (ART) with known RM analysing the possible benefits of G-CSF application. From January 2002 to December 2010, 127 patients (199 cylces) with RM (at least 2 early miscarriages) 49 (72 cycles) receiving G-CSF and 78 (127 cycles) controls receiving either no medication (subgroup 1) or Cortisone, intravenous immunoglobulins or low molecular weight heparin (subgroup 2) undergoing ART for in vitro fertilisation/intracytoplasmic sperm injection were analysed. G-CSF was administered weekly once (34 Mill) in 11 patients, 38 patients received 2 × 13 Mill G-CSF per week until the 12th week of gestation. Statistical analysis was performed with SPSS for Windows (19.0), p < 0.05 significant. The mean age of the study population was 37.3 ± 4.4 years (mean ± standard deviation) and differed not significantly between patients and subgroups. However, the number of early miscarriages was significantly higher in the G-CSF group as compared to the subgroups (G-CSF 2.67 ± 1.27, subgroup 1 0.85 ± 0.91, subgroup 2 0.64 ± 0.74) and RM patients receiving G-CSF had significantly more often a late embryo transfer (day 5) (G-CSF 36.7 %, subgroup 1 12.1 %, subgroup 2 8.9 %). The LBR of patients and the subgroups differed significantly (G-CSF 32 %, subgroup 1 13 %, subgroup 2 14 %). Side effects were present in less than 10 % of patients, consisting of irritation at the injection side, slight leukocytosis, rise of the temperature (<38 °C), mild bone pain and hyperemesis gravidarum. None of the newborn showed any kind of malformations. According to our data, G-CSF seems to be a safe and promising immunological treatment option for RM patients. However, with regard to the retrospective setting and the possible bias of a higher rate of late embryo transfers in the G-CSF group additional studies are needed to further strengthen our results.
Gesehen am 31.01.2022